2018
DOI: 10.3389/fendo.2018.00181
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Aerobic Exercise Impairment in Diabetes: A Narrative Review

Abstract: The prevalence of diabetes in the United States and globally has been rapidly increasing over the last several decades. There are now estimated to be 30.3 million people in the United States and 422 million people worldwide with diabetes. Diabetes is associated with a greatly increased risk of cardiovascular mortality, which is the leading cause of death in adults with diabetes. While exercise training is a cornerstone of diabetes treatment, people with diabetes have well-described aerobic exercise impairments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 124 publications
(121 reference statements)
1
25
0
2
Order By: Relevance
“…Our 12-month follow-up assessment revealed that the further improvement after end of CR was reduced in diabetic patients when compared to non-diabetic patients. The poorer long-term development of VO 2 peak in our elderly diabetic patients was also found previously [37] and may reflect the natural disease progression that is associated with reduced cardiovascular fitness [38]. The previously reported relationship between glycemic control with gain in VO 2 peak [39] was not found in the present study, however, the assessment of HbA1c may not have allowed us to assess short term changes in glycemic control.…”
Section: Vosupporting
confidence: 41%
“…Our 12-month follow-up assessment revealed that the further improvement after end of CR was reduced in diabetic patients when compared to non-diabetic patients. The poorer long-term development of VO 2 peak in our elderly diabetic patients was also found previously [37] and may reflect the natural disease progression that is associated with reduced cardiovascular fitness [38]. The previously reported relationship between glycemic control with gain in VO 2 peak [39] was not found in the present study, however, the assessment of HbA1c may not have allowed us to assess short term changes in glycemic control.…”
Section: Vosupporting
confidence: 41%
“…During a range of pathological processes and in all tissues and organs, NO was determined to be the primary molecule linked to the regulation of vascular endothelium tissue, and exercise may correct alterations in the bioavailability of this radical. Enzymatic production of NO by endothelial nitric oxide synthase has a regulatory role in endothelial dysfunction (54) and NO participates in vascular adaptation to exercise (55,56). Therefore, the association between NO and different nitric oxide synthases in diabetic tissues requires examination.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has characterized many individual impairments in key cardiac and vascular measures that are associated with CRF impairment in T2D, such as insulin resistance, endothelial dysfunction, decreased myocardial perfusion with exercise, abnormally increased pulmonary capillary wedge pressure (PCWP), decreased limb blood flow, and skeletal muscle mitochondrial dysfunction [27]. Some researchers highlight that being the reasons for which these abnormalities arise, caused by several factors, makes it unlikely that a single therapeutic approach will resolve the entire problem.…”
Section: Exercise Benefits On Patients With Type 2 Diabetesmentioning
confidence: 99%
“…Diabetes patient usually has physiologic exercise limitations and decreased cardiorespiratory fitness (CRF). More exactly, when compared with people with and without diabetes, the first ones can present 20% lower maximal oxygen uptake (VO 2 max) [27]. This can be a problem for those patients once a reduced VO 2 max is linked to increased cardiovascular mortality [34].…”
Section: Exercise Benefits On Patients With Type 2 Diabetesmentioning
confidence: 99%